General recommendations to the colorectal surgeon during the COVID-19 pandemic - Campos, Fábio Guilherme (Journal of Coloproctology, 2020)
The COVID-19 pandemic has shown our country in an unfavorable light, as Brazil has reported the second highest number of deaths to date. When the social isolation phase is finished, professional activities (including the medical ones) will resume their routines and the specialist must be updated in order to provide effective and safe care. Although many published recommendations are based on low levels of evidence, disclosing them has become necessary, since the coronavirus infection may affect operative outcomes. Overall, it is suggested that physicians adopt preventive measures, starting with the medical appointment, and extending them to the surgical procedure. Furthermore, it is also necessary to provisionally change criteria for operative indications and conducts. Currently, postponing elective surgeries seems to be a universally agreed decision. Moreover, we need to establish the early diagnosis of the viral infection, before or after the surgery. Several safety measures related to minimally-invasive procedures have been reported, disclosing the risks of aerosol dissemination by the pneumoperitoneum and smoke from energy-powered devices. The present article aimed to bring to the colorectal surgeon the current recommendations and general safety measures in order to prevent infection dissemination, to improve surgical planning in terms of timing and specific technical aspects.